2017
DOI: 10.1111/jdi.12636
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is associated with incident albuminuria in patients with type 2 diabetes: A retrospective observational study

Abstract: Sarcopenia, defined as age‐related loss of skeletal muscle mass and function, increases the risk of albuminuria. However, it has still unknown whether sarcopenia could increase the risk for the progression of albuminuria. A total 238 patients with type 2 diabetes (mean age 64 ± 12 years; 39.2% women) were studied in the present retrospective observational study. The prevalence of sarcopenia was 17.6%. During the median follow‐up period of 2.6 years, albuminuria was measured 5.8 ± 1.8 times, and progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 24 publications
5
42
1
Order By: Relevance
“…In a previous study, the prevalence of sarcopenia in older patients with diabetes was 19% in men and 27% in women, which is similar to that observed in the present study . In another study that targeted diabetes patients, the prevalence of sarcopenia was 17.6% . Presumably, differences in participant age, comorbidities and sarcopenia definition strongly influenced the outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a previous study, the prevalence of sarcopenia in older patients with diabetes was 19% in men and 27% in women, which is similar to that observed in the present study . In another study that targeted diabetes patients, the prevalence of sarcopenia was 17.6% . Presumably, differences in participant age, comorbidities and sarcopenia definition strongly influenced the outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…7 In another study that targeted diabetes patients, the prevalence of sarcopenia was 17.6%. 24 Presumably, differences in participant age, comorbidities and sarcopenia definition strongly influenced the outcomes. Compared with patients without diabetes, those with diabetes had a higher prevalence of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, no study has investigated the potential association of sarcopenia with the rate of decline in eGFR. In addition to our previous finding of a significant association between sarcopenia and incident albuminuria , in the present study, we showed that sarcopenia was independently associated with the annual rate of decline in eGFR after adjustment for confounding variables in people with type 2 diabetes. Although low eGFR is a confounding factor in the relationships between sarcopenia and rate of decline in eGFR , the association remained unchanged even in the sensitivity analysis of people with eGFR ≥60 ml/min/1.73m 2 .…”
Section: Discussionsupporting
confidence: 77%
“…This is in line with the association of albuminuria with sarcopenia, a condition characterized by decreases in muscle mass, strength, and function, which was reported in previous studies including individuals without diabetes. [35][36][37] Albuminuria reflects endothelial dysfunction and generalized vascular damage, [38][39][40] which may affect muscle metabolism leading to reduced muscle strength. Impaired microcirculation, microinflammation, and oxidative stress within the muscle capillaries may be involved in this association.…”
Section: Discussionmentioning
confidence: 99%